ALTERNATIVE SISTEM PENGAWASAN PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) DALAM MEWUJUDKAN SHARIAH COMPLIANCE - Hidayat, Farid (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
There are two types of financial institutions, namely bank and non Bank, which are operate under shariah and conventional system. Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) is one of the financial institutions is not a Bank that operates with the Sharia system. In conducting its operations, whether Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) runs its operations in accordance with sharia, or not. In this case, the rule of Sharia Supervisory Board is very crucial to ensure that Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) has fulfil the shariah principle. Although they have Sharia Supervisory Board, but there are still many Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) which are not comply with syariah principles. This problems is caused by weaknesses of Shariah Supervisory Board (DPS) and Hassle System from recruitment to the accountability of the Shariah Supervisory Board. Therefore, there is the thought of the author's alternative surveillance system Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) in realizing the shariah compliance.